2014
DOI: 10.2146/ajhp130495
|View full text |Cite
|
Sign up to set email alerts
|

Integrated clinical and specialty pharmacy practice model for management of patients with multiple sclerosis

Abstract: An integrated pharmacy practice model that includes an interdisciplinary team of physicians, nurses, and pharmacists improved patient compliance with MS therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 7 publications
(15 reference statements)
1
31
0
Order By: Relevance
“…[47][48][49] These new outpatient operations have the potential for improved medication access for patients, better continuity of care and integration, improved patient outcomes, and a new revenue stream for the health system. Since most specialty drugs are still widely available to hospitals and clinics, opportunities exist for outpatient specialty pharmacies in therapeutic categories that are relevant to the health system, such as oncology, inflammatory conditions, multiple sclerosis, transplant, and infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] These new outpatient operations have the potential for improved medication access for patients, better continuity of care and integration, improved patient outcomes, and a new revenue stream for the health system. Since most specialty drugs are still widely available to hospitals and clinics, opportunities exist for outpatient specialty pharmacies in therapeutic categories that are relevant to the health system, such as oncology, inflammatory conditions, multiple sclerosis, transplant, and infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 The advancements in treatment options for MS has drastically increased the time providers must allocate to medication management. 3,4 Most DMTs are classified as specialty medications because of their cost, medication access restrictions, specialized administration training and requirements for ongoing monitoring. With the cost of DMTs increasing at an exponential rate, coverage denials are occurring more frequently, often requiring multiple steps for medication approval.…”
Section: Introductionmentioning
confidence: 99%
“…5 The complexity of this process and the substantial amount of time required for medication management necessitates the involvement of a medication expert, such as a clinical pharmacist, in MS patient care. 3,5 Historically, there was no formal process dedicated to medication therapy management (MTM) for patients with MS seen at the Grady Health System (GHS) neurology clinic.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of health systems have developed internal specialty pharmacies to alleviate barriers to accessing specialty medications, improve appropriate utilization and optimization of specialty agents, and streamline transitions in care [13][14][15][16][17]. Several studies have demonstrated the benefit of pharmacists in maintaining continuity of care for patients transitioning from one healthcare setting to another [18,19].…”
Section: Introductionmentioning
confidence: 99%